Photosensitive resin for photocuring DLP (Digital Light Processing) technology as well as composite material, preparation method and application thereof

By using mechanically chemically synthesized photosensitive resin and its modified nanofiller-enhanced composite materials in DLP 3D printing, the problems of poor mechanical properties and poor corrosion resistance after photosensitive resin molding are solved, and the effects of high mechanical properties and chemical corrosion resistance are achieved.

CN119708380AInactive Publication Date: 2025-03-28SHENYANG JUSHENG NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510232222.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing photosensitive resins used for DLP 3D printing have poor mechanical properties after forming, prone to brittle fracture, and have poor corrosion resistance, which cannot compete with traditional 3D printing technology.

Method used

Photosensitive resin composites were prepared by mechanochemical methods and enhanced with modified nanofillers such as silica, aramid fibers and Al2O3.

Benefits of technology

It improves the mechanical properties and chemical corrosion resistance of the photosensitive resin, can maintain stability in acid, alkali and salt environments, and is low in cost and simple in preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708380A_ABST
    Figure CN119708380A_ABST
Patent Text Reader

Abstract

The invention discloses photosensitive resin for a photocuring DLP (Digital Light Processing) technology and a composite material, a preparation method and application thereof, and belongs to the field of photocuring 3D (Three-Dimensional) printing. The preparation method comprises the following steps: by taking epoxy resin as matrix resin through a mechanochemical method, adding a catalyst, a polymerization inhibitor, a photoinitiator and a diluent to prepare photosensitive resin for a photocuring DLP (Digital Light Processing) technology, and selectively adding modified nano silicon dioxide, modified nano aramid fiber and modified nano Al2O3 as fillers to obtain a composite material of the photosensitive resin. The composite material of the photosensitive resin has excellent photocuring performance, mechanical performance and corrosion resistance, parts of complex structures can be rapidly formed in the DLP technology, and the production efficiency and the product quality are remarkably improved. In addition, the added modified nano silicon dioxide particles, modified nano aramid fibers and modified nano Al2O3 enhance the mechanical properties and environmental stability of the resin, so that the resin has wide application prospects in the fields of aerospace, electronic packaging, biomedical treatment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocuring 3D printing, and relates to a photosensitive resin used for photocuring DLP technology, a composite material thereof, a preparation method and an application thereof. Background Art

[0002] Digital Light Processing (DLP) technology is one of the photocuring 3D printing technologies with the highest printing accuracy. Compared with the point-by-point scanning curing method using a digital projection laser beam, DLP technology has a short curing time per layer and a fast printing speed. Due to its high resolution, it has a higher printing accuracy. Therefore, finer details and smoother surface quality can be obtained.

[0003] At present, the more mature photosensitive resins used for DLP 3D printing mainly include: epoxy acrylate resins, polyurethane acrylate resins, polyester acrylate resins. In the process of DLP printing, they have the following problems to be solved: poor mechanical properties after molding. Due to the low cross-linking density in the resin or the characteristics of the molecular chain structure, the strength and toughness of the photosensitive resin are poor, and brittle fracture is prone to occur. And the corrosion resistance is poor. In acid, alkali, salt and other environments, it is easy to corrode, causing its performance to deteriorate. This results in the performance of the molded samples being unable to compete with traditional 3D printing technologies such as injection molding and extrusion processes. Therefore, it is very necessary to develop a simple and reliable photosensitive resin for photocuring DLP technology printing. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a photosensitive resin and a composite material thereof, a preparation method and an application thereof for photocuring DLP technology. A photosensitive resin is synthesized by a mechanochemical method, and a modified nanofiller is used to enhance it to prepare a photosensitive resin composite material. Specifically, there are three types. The first type: using a dilution method, adding silica / epoxy resin colloid to epoxy resin to prepare a synthetic photosensitive resin / silicon dioxide composite material. The second type: using a top-down method to synthesize modified nano-aramid fiber, and then mechanically stirring and ultrasonically mixing with the independently synthesized photosensitive resin to synthesize a photosensitive resin / aramid fiber composite material. The third type: using a mechanochemical method to prepare modified nano-Al2O3, and preparing a photosensitive resin / Al2O3 composite material. The prepared photosensitive resin and its corresponding photosensitive resin composite material can be printed with a photocuring 3D printer. After the sample is subjected to mechanical and corrosion resistance tests, it meets the strength and toughness requirements and can resist acid and alkali corrosion.

[0005] The photosensitive resin used for the photocurable DLP technology of the present invention comprises raw materials including epoxy resin matrix, acrylic acid substance, catalyst, polymerization inhibitor, photoinitiator and diluent.

[0006] The epoxy resin matrix is ​​selected from bisphenol A epoxy resin, more preferably one or more of E51 epoxy resin, E44 epoxy resin, F-51 epoxy resin or F-41 epoxy resin.

[0007] The acrylic acid substance is acrylic acid (AA) and / or acrylic acid (GAA).

[0008] The catalyst is preferably one or more of tetraethylammonium bromide, triphenylantimony and triethylamine.

[0009] The polymerization inhibitor is preferably one or more of p-hydroxyanisole (MEHQ), hydroquinone, and p-methoxyphenol.

[0010] The photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and / or 1-hydroxy-cyclohexyl benzophenone (184).

[0011] The diluent is tripropylene glycol diacrylate (TPGDA) and / or 1,6-hexanediol diacrylate (HDDA).

[0012] By mass ratio, photosensitive resin used in photocurable DLP technology: catalyst: inhibitor: photoinitiator: diluent = 100: (0.1~1): (0.01~1): (2~5): (15~25). By mass ratio, epoxy resin matrix: acrylic acid material = (5~9): (1~5).

[0013] A method for preparing a photosensitive resin for photocurable DLP technology of the present invention comprises the following steps: S1: heating the epoxy resin matrix, adding acrylic substances, catalysts, and polymerization inhibitors, performing a gradient temperature increase reaction, and then cooling the temperature to obtain epoxy acrylate; S2: Epoxy acrylate, photoinitiator and diluent are mixed and dispersed by ultrasonic to obtain a photosensitive resin for photocurable DLP technology.

[0014] In the S1, the heating temperature is 80-90°C; the reaction temperature of the gradient temperature increase reaction is 90-100°C and kept for 1-3h, then the temperature is increased by 10°C and kept for 0.5-2h, and then cooled to 60-70°C.

[0015] In the above-mentioned S2, the mixing and stirring is performed for more than 5 minutes, and the ultrasonic dispersion is performed for more than 30 minutes.

[0016] The photosensitive resin used for the light-curing DLP technology of the present invention is prepared by adopting the above preparation method.

[0017] The composite material of a photosensitive resin for photocuring DLP technology of the present invention comprises a photosensitive resin for photocuring DLP technology and a modified nano filler as raw materials, wherein the modified nano filler is selected from one or more of modified nano silicon dioxide, modified nano aramid fiber and modified nano Al2O3; according to the selection of the modified nano filler, the composite material of the photosensitive resin for photocuring DLP technology is one of a photosensitive resin / silicon dioxide composite material, a photosensitive resin / aramid fiber composite material and a photosensitive resin / Al2O3 composite material; The composite material of the photosensitive resin used for the light-curing DLP technology has a tensile strength of 36.89-46.91 MPa and an elongation at break of 22.7%-30.2%. It has relatively excellent corrosion resistance in acid, alkali, salt and other environments, and has excellent mechanical properties and chemical corrosion resistance.

[0018] The present invention provides a method for preparing a composite material of a photosensitive resin for photocuring DLP technology, which is prepared by one of the following preparation methods: (1) When the composite material of the photosensitive resin used for the light-curing DLP technology is a photosensitive resin / silicon dioxide composite material, the preparation method used is: According to the ratio, the epoxy resin matrix and the silica / epoxy resin mixed sol are mixed to obtain a diluted silica / epoxy resin mixed sol, which is then substituted with the epoxy resin matrix to obtain a photosensitive resin / silicon dioxide composite material according to the preparation method of the photosensitive resin for the photocurable DLP technology. Among them, the mass percentage of silica in the photosensitive resin / silicon dioxide nanocomposite material is 1% to 10%.

[0019] The silica / epoxy resin mixed sol is spherical nano silica particles (Nanopox F400) provided by Hanse Chemie AG, Germany, as a colloidal sol (40% wt%) in epoxy resin.

[0020] (2) When the composite material of the photosensitive resin used for the light-curing DLP technology is a photosensitive resin / aramid fiber composite material, the preparation method adopted is: The modified nano-aramid fiber suspension is repeatedly washed with deionized water and a solvent, the collected modified nano-aramid fiber (ANF) is added to a diluent solution, and the obtained mixture is dispersed by an ultrasonic cell disruptor to obtain uniformly dispersed modified nano-aramid fiber (ANF); The modified nano-aramid fiber and the photosensitive resin used for the photocurable DLP technology are mixed evenly, and then heated and vacuum degassed to remove the solvent to obtain a photosensitive resin / aramid fiber composite material, wherein the mass percentage of the aramid fiber in the photosensitive resin / aramid fiber composite material is less than or equal to 2%.

[0021] The modified nano-aramid fiber suspension is prepared by a top-down method.

[0022] The specific preparation method is: the modified nano-aramid fiber is synthesized by a bottom-up method: In a nitrogen atmosphere, N-methylpyrrolidone (NMP) was heated to 100 ◦C and CaCl2 was added under stirring. According to the solid-liquid ratio, CaCl2: N-methylpyrrolidone (NMP) = (5~10g) : (100~300ml); after CaCl2 was dissolved, the reaction system was cooled to 0-5℃ using an ice-water bath; rubber accelerator (PPD) was added under stirring at 400 rpm; according to the molar ratio, CaCl2: PPD = (0.04~0.1): 0.01. After PPD was dissolved, terephthaloyl chloride (TPC) was added, where the molar ratio of PPD to TPC = 1:1.05, and polycondensation was carried out by stirring at a speed of 1000~2000 rpm. Stop stirring when the Weissenberg effect occurs (the solution is not thrown outward, but is pulled toward the stirring rod and rises around it). Then, NMP was added in an amount 2 to 6 times the amount added for the first time, and the mixture was stirred at 1000 to 2000 rpm for 5 to 10 minutes to disperse the gel into a free-flowing ANF / NMP uniform dispersion. Finally, the dispersion was slowly added to sufficient deionized water (10 times the volume of the ANF / NMP uniform dispersion) and stirred at 1000 to 2000 rpm for 10 to 20 minutes to obtain an ANF / NMP / water suspension as a modified nano-aramid fiber suspension.

[0023] The above-mentioned p-phenylenediamine (PPD) and terephthaloyl chloride (TPC) are modified surfactants.

[0024] The solvent is ethanol and / or acetone, preferably acetone.

[0025] The dispersion time of the ultrasonic cell disruptor is 30 to 60 minutes.

[0026] The uniform mixing is performed by magnetic stirring for 30 to 60 minutes.

[0027] The heated vacuum degassing is vacuum degassing at 50-70°C for more than 24 hours.

[0028] The diluent is TPGDA and / or HDDA.

[0029] (3) When the composite material of the photosensitive resin used for the light-curing DLP technology is a photosensitive resin / Al2O3 composite material, the preparation method adopted is: The modified nano-Al2O3 and the photosensitive resin used for the light-curing DLP technology are mixed and ultrasonically dispersed to obtain a photosensitive resin / Al2O3 composite material, wherein the mass percentage of Al2O3 in the photosensitive resin / Al2O3 composite material is 1% to 5%.

[0030] The modified nano-Al2O3 is prepared by a mechanochemical method. The specific preparation method is as follows: weigh 5g of nano-Al2O3 on a balance, add it to a 250mL three-necked flask, then add 100mL of a mixture of a prepared dodecylbenzenesulfonic acid aqueous solution and toluene (ratio 1:1), stir at a stirring speed of 500rpm for 48h at room temperature, add 0.5g of a free radical initiator, then add 20mL of methyl methacrylate (MMA), heat the oil bath to 60°C, and continue the reaction for 12h. After the reaction is completed, filter to obtain a solid, wash it three times with anhydrous ethanol, wash the surface-modified nano-Al2O3 with anhydrous ethanol three times in a methanol solution, then put it into a 70°C drying oven for 3h, take it out after cooling, grind it with a mortar for standby use, and obtain modified nano-Al2O3.

[0031] The ultrasonic dispersion has an ultrasonic power of 50-60W, an ultrasonic dispersion time of more than 24h, and an ultrasonic temperature of less than 40°C.

[0032] The composite material of the photosensitive resin used in the light-curing DLP technology of the present invention is used as a raw material of the light-curing DLP technology to print out application structural parts or test structural parts by using the light-curing DLP technology.

[0033] The photosensitive resin used for photocurable DLP technology and its composite material, preparation method and application of the present invention have the following beneficial effects: 1. The present invention uses epoxy resin as a matrix and adds modified nanofillers to synthesize a composite material of photosensitive resin for photocuring DLP technology by a mechanochemical method. The composite material has low cost, simple preparation process, high mechanical strength and chemical corrosion resistance. The photosensitive resin prepared using epoxy resin can be used to prepare high-precision test samples using a photocuring 3D printer for performance testing of aircraft structural parts. The safety status of aircraft structural parts can be judged based on a comprehensive analysis of the collected data. Because the photosensitive resin has a high printing accuracy, it can also be directly used for relatively precise and small structural parts.

[0034] 2. Aiming at the requirements of mechanical strength and corrosion resistance of aircraft structural parts, a method for preparing photosensitive resin is proposed based on the principle of photocuring. A photocuring printer can be used to print out a test model with the same structure and precision as the aircraft structural parts, and a corresponding test scheme is designed: (1) A self-made photosensitive resin and its composite material are used to print out tensile test pieces by a photocuring printer, and the tensile strength range is estimated by a tensile testing machine; (2) The corrosion resistance of the self-made photosensitive resin and its composite material in an acid, alkali and salt environment is tested by an electrochemical workstation; (3) Finite element simulation is performed on the tensile parts after curing of the photosensitive resin and its composite material to determine their fracture position; 3. The photosensitive resin of the present invention utilizes its rapid curing characteristics to rapidly manufacture parts of complex shapes through 3D printing technology, thereby shortening the R&D cycle and production time. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 :Schematic diagram of the preparation process of photosensitive resin and its composite materials used in light-curing DLP technology; Figure 2 :Tensile performance curve of photosensitive resin / silicon dioxide composite material used for photocuring DLP technology; Figure 3 :Tensile performance curve of photosensitive resin / aramid fiber composite material used for photocuring DLP technology; Figure 4 :Tensile performance curve of photosensitive resin / Al2O3 composite material used in light-curing DLP technology; Figure 5 : Schematic diagram of finite element simulation of tensile failure of composite materials of photosensitive resin used in light-curing DLP technology. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below in conjunction with embodiments.

[0037] The present invention is further described in detail below in conjunction with embodiments.

[0038] In the following embodiments, the test samples printed by a 3D printer were tested for tensile strength by a universal tensile testing machine, and for corrosion resistance by an electrochemical workstation; In the following embodiments, the tensile test specimens and finite element simulation specimens used are formulated in accordance with the national standard ISO 37-2005; In the following examples, the data acquisition device uses a universal test tensile machine and an electrochemical workstation; In the following examples, the photoinitiator is one or two of TPO, 184; In the following examples, the epoxy resin used is bisphenol A type epoxy resin; In the following examples, the solvent used is one or both of ethanol and acetone; In the following examples, the acid, alkali and salt environments used in the electrochemical workstation are 5% H2SO4, 5% NaOH and 5% NaCl in concentration, respectively.

[0039] The following embodiments include the preparation process of photosensitive resin and composite materials used in light-curing DLP technology, and the schematic diagram of the process is shown in FIG. Figure 1 .

[0040] Example 1 A method for preparing a photosensitive resin for photocuring DLP technology comprises the following steps: Step 1: 21.3 g of epoxy resin E51 was placed in a beaker and heated to 85°C in an oil bath; secondly, 8.7 g, 0.1 g and 0.075 g of acrylic acid, catalyst and inhibitor mixture were slowly dripped into the beaker using a dropper. Then the temperature was raised to 95°C and maintained for 2 hours, then raised to 105°C and maintained for 1 hour, and finally the system temperature was lowered to 60°C, and a mixture of 0.801 g of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and photoinitiator 1-hydroxy-cyclohexyl benzophenone (184) was added, and then 8.1 g of diluent 1,6-hexanediol diacrylate (HDDA) was added to the mixture, and mechanical stirring was performed at a speed of 2000 rpm for 5 minutes, and then ultrasonic dispersion was performed in an ultrasonic cleaner for 30 minutes, and finally vacuumed in a vacuum oven to remove bubbles generated during stirring, thereby obtaining a prepared photosensitive resin for photocurable DLP technology.

[0041] Step 2: Place the prepared photosensitive resin for photocuring DLP technology into a photocuring 3D printer, set the printing parameters, cure it into a test sample, wash off the uncured resin on the surface with a solvent, and test its performance.

[0042] Example 2 A method for preparing a composite material of a photosensitive resin for photocuring DLP technology comprises the following steps: Step 1: The silica / epoxy resin mixed colloid is diluted with epoxy resin, and the silica is diluted to a mass ratio of 2.0%, and heated to 85°C in an oil bath; secondly, a catalyst is added, and the mass ratio of epoxy resin: acrylic acid is 9:1. The mass fraction of the catalyst added to the prepared composite material is 1%, and the mass fraction of the inhibitor added to the prepared composite material is 0.05%. The temperature is raised to 95°C and kept for two hours, and then the temperature is raised to 105°C and kept for one hour. Finally, the system temperature is lowered to 60°C, and a photoinitiator with a mass fraction of 5% and a diluent with a mass fraction of 20% are added. The system is vigorously mechanically stirred for 5 minutes, and then placed in an ultrasonic cleaner for ultrasonic dispersion for 30 minutes. Finally, the system is placed in a vacuum oven and evacuated to remove bubbles generated during the stirring process to obtain a photosensitive resin / silicon dioxide nanocomposite material. Step 2: The prepared photosensitive resin / silicon dioxide nanocomposite material was placed in a light-curing 3D printer and cured into a test sample. The uncured resin on the surface was washed off with a solvent, and its performance was tested.

[0043] Example 3 A method for preparing a composite material of a photosensitive resin for photocuring DLP technology comprises the following steps: Step 1: The silica / epoxy resin mixed colloid is diluted with epoxy resin, and the silica is diluted to a mass ratio of 4.0%, and heated to 85°C in an oil bath; secondly, a catalyst is added, and the mass ratio of epoxy resin: catalyst = 8:2, and the mass fraction of the catalyst is 1%, and the mass fraction of the inhibitor is 0.05%. The temperature is raised to 95°C and kept for two hours, and then the temperature is raised to 105°C and kept for one hour. Finally, the system temperature is lowered to 60°C, and a photoinitiator with a mass fraction of 5% and a diluent with a mass fraction of 20% are added. The system is mechanically stirred vigorously for 5 minutes, and then placed in an ultrasonic cleaner for ultrasonic dispersion for 30 minutes. Finally, the system is placed in a vacuum oven for evacuation to remove bubbles generated during the stirring process to obtain a photosensitive resin / silicon dioxide nanocomposite material; Step 2: The prepared photosensitive resin / silicon dioxide nanocomposite material was placed in a light-curing 3D printer and cured into a test sample. The uncured resin on the surface was washed off with a solvent, and its performance was tested.

[0044] Example 4 A method for preparing a composite material of a photosensitive resin for photocuring DLP technology comprises the following steps: Step 1: The silica / epoxy resin mixed colloid is diluted with epoxy resin, and the silica is diluted to a mass ratio of 6.0%, and heated to 85°C in an oil bath; secondly, a catalyst is added, and the mass ratio of epoxy resin: catalyst = 7:3, the mass fraction of the catalyst added to the prepared composite material is 1%, and the mass fraction of the inhibitor to the prepared composite material is 0.05%, the temperature is increased to 95°C and kept for two hours, and then the temperature is increased to 105°C and kept for one hour, and finally the system temperature is lowered to 60°C, and a photoinitiator with a mass fraction of 5% and a diluent with a mass fraction of 20% are added, and the mixture is vigorously mechanically stirred for 5 minutes, and then placed in an ultrasonic cleaner for ultrasonic dispersion for 30 minutes, and finally placed in a vacuum oven for evacuation to remove bubbles generated during the stirring process, and a photosensitive resin / silicon dioxide nanocomposite material is obtained; Step 2: The prepared photosensitive resin / silicon dioxide nanocomposite material was placed in a light-curing 3D printer and cured into a test sample. The uncured resin on the surface was washed off with a solvent, and its performance was tested.

[0045] Example 5 A method for preparing a composite material of a photosensitive resin for photocuring DLP technology comprises the following steps: Step 1: The silica / epoxy resin mixed colloid is diluted with epoxy resin to a mass ratio of 8.0%, and heated to 85°C in an oil bath; secondly, a catalyst is added, according to the mass ratio, epoxy resin: catalyst = 6:4, the mass fraction of the catalyst added to the prepared composite material is 1%, and the mass fraction of the inhibitor to the prepared composite material is 0.05%, the temperature is increased to 95°C and kept for two hours, and then the temperature is increased to 105°C and kept for one hour, and finally the system temperature is lowered to 60°C, 5% of the mass fraction of the photoinitiator and 20% of the mass fraction of the diluent are added, and the mixture is vigorously mechanically stirred for 5 minutes, and then placed in an ultrasonic cleaner for ultrasonic dispersion for 30 minutes, and finally placed in a vacuum oven for evacuation to remove bubbles generated during the stirring process to obtain a photosensitive resin / silicon dioxide nanocomposite material; Step 2: The prepared photosensitive resin / silicon dioxide nanocomposite material was placed in a light-curing 3D printer and cured into a test sample. The uncured resin on the surface was washed off with a solvent, and its performance was tested.

[0046] Example 6 A method for preparing a composite material of a photosensitive resin for photocuring DLP technology comprises the following steps: Step 1: The silica / epoxy resin mixed colloid is diluted with epoxy resin to a mass ratio of 10.0%, and heated to 85°C in an oil bath; the catalyst is then added, and the mass ratio of epoxy resin: catalyst = 1:1, the mass fraction of the catalyst added to the prepared composite material is 1%, and the mass fraction of the inhibitor to the prepared composite material is 0.05%, the temperature is raised to 95°C and kept for two hours, and then the temperature is raised to 105°C and kept for one hour, and finally the system temperature is lowered to 60°C, and a photoinitiator with a mass fraction of 5% and a diluent with a mass fraction of 20% are added, and the mixture is vigorously mechanically stirred for 5 minutes, and then placed in an ultrasonic cleaner for ultrasonic dispersion for 30 minutes, and finally placed in a vacuum oven for evacuation to remove bubbles generated during the stirring process, and a photosensitive resin / silicon dioxide nanocomposite material is obtained; Step 2: The prepared photosensitive resin / silicon dioxide nanocomposite material was placed in a light-curing 3D printer and cured into a test sample. The uncured resin on the surface was washed off with a solvent, and its performance was tested.

[0047] Example 7 A method for preparing a composite material of a photosensitive resin for photocuring DLP technology comprises the following steps: Step 1: Modified nano-aramid fibers were synthesized using a bottom-up approach. The specific method is as follows: (100-300 mL) N-methylpyrrolidone (NMP) was heated to 100 °C under nitrogen atmosphere, and (5-10 g) CaCl2 was added under stirring. After CaCl2 was dissolved, the reaction system was cooled to 0-5 °C using an ice-water bath; 0.01 mol of rubber accelerator (PPD) was added under stirring at 400 rpm. After PPD was dissolved, terephthaloyl chloride (TPC) (molar ratio of PPD to TPC = 1:1.05) was added and polycondensed at 2000 rpm. Stirring was stopped when the Weissenberg effect appeared (the solution was not thrown outward, but was pulled toward the stirring rod and rose around it). Then, 600 mL NMP was added and the mixture was stirred at 2000 rpm for 5 minutes to disperse the gel into a free-flowing ANF / NMP uniform dispersion. Finally, the dispersion was slowly added into sufficient deionized water (10 times the volume of the ANF / NMP dispersion) and stirred at 2000 rpm for 10 min to obtain an ANF / NMP / water suspension.

[0048] Step 2: The modified nano-aramid fiber suspension obtained in step 1 was repeatedly washed with deionized water and acetone, the collected modified nano-aramid fibers were added to the diluent solution, and the mixture was dispersed for 30 minutes using an ultrasonic cell disruptor. Subsequently, the prepared pure photosensitive resin was mixed in different proportions, with the mass ratio of the modified nano-aramid fiber being 0.1-2%, and magnetically stirred for 30 minutes. The obtained mixture was degassed under vacuum conditions at 60°C for 24 hours to remove residual acetone, and a photosensitive resin / nano-aramid fiber composite material was obtained.

[0049] Step 3: The prepared photosensitive resin / nano-aramid fiber composite material was placed in a light-curing 3D printer and cured into a test sample. The uncured resin on the surface was washed off with a solvent, and its performance was tested.

[0050] Example 8 A method for preparing a composite material of a photosensitive resin for photocuring DLP technology, comprising the following steps: Step 1: Weigh 5g of nano-Al2O3 on a balance, add it to a 250mL three-necked flask, then add 100mL of a mixture of a prepared aqueous solution of dodecylbenzenesulfonic acid and toluene (volume ratio 1:1), stir at 500rpm for 48h at room temperature, add 0.5g of free radical initiator azobisisobutyronitrile (AIBN), then add 20mL of methyl methacrylate (MMA), heat the oil bath to 60°C, and continue the reaction for 12h. After the reaction is completed, filter to obtain a solid, wash it three times with anhydrous ethanol, wash the surface-modified nano-Al2O3 with anhydrous ethanol three times in a methanol solution, then put it in a 70°C drying oven and dry it for 3h, take it out after cooling, grind it with a mortar for use, and obtain modified nano-Al2O3; Step 2: The modified nano-Al2O3 was added into the photosensitive resin used for the light-curing DLP technology at a mass percentage of 1%, 2%, 3%, 4% and 5%, and dispersed for 24 hours at a power of 60W using a CNC ultrasonic cleaner and the temperature was controlled at 40°C to obtain a photosensitive resin / Al2O3 composite material.

[0051] Comparative Example 1 A method for preparing a photosensitive resin for photocuring DLP technology is the same as that of Examples 2 to 8, except that: graphene nanosheets and independently synthesized pure photosensitive resin are mechanically mixed, and the method is used to prepare a photosensitive composite material to enhance the performance of the pure photosensitive resin. However, the graphene nanosheets cannot be relatively evenly dispersed in the photosensitive resin, and cannot form a strong interface with the photosensitive resin. It is easy to form agglomerations and stress concentration points in the photosensitive resin, and cannot effectively enhance the mechanical and corrosion resistance of the pure photosensitive resin. In addition, graphene itself is black, and excessive addition greatly affects the molding accuracy of the photosensitive resin.

[0052] Comparative Example 2 A nano-silica / polyacrylate modified epoxy resin adhesive, the preparation method of which is prepared by the preparation method of CN102703009B, which uses polyacrylate modified nano-silica, mixes with epoxy resin, and then adds a photoinitiator. It cannot be used as a raw material for light-cured DLP technology because the adhesive does not have a photoinitiator and can only be thermally cured but not light-cured. The photoinitiator can cause epoxy acrylate to undergo a cross-linking reaction under ultraviolet irradiation, thereby curing.

[0053] Comparative Example 3 A UV-curable acrylic-epoxy resin film is prepared by the preparation method of CN116640527A. The difference between the preparation method of the embodiment of the present invention and the preparation method of the embodiment of the present invention is that the above method requires a solvent and an epoxy resin curing agent during the preparation process, but the present method does not need them, and the catalysts used in the two methods are different. The material prepared by the method has good electrical and thermal conductivity, and the material prepared by the present invention has excellent mechanical properties and corrosion resistance.

[0054] Application Examples The photosensitive resin and its composite materials were subjected to tensile tests. The tensile test pieces used were standard pieces. The tensile performance curves are shown in Figures 2~4, it can be seen from the figure that with the addition of silica, the tensile strength of the composite material of the photosensitive resin gradually increases. When the addition amount of silica reaches 6%, the mechanical properties of the composite material of the photosensitive resin reach the maximum. When the addition amount of silica exceeds this optimal mass ratio, the tensile strength of the composite material of the photosensitive resin decreases but is still higher than that of pure photosensitive resin. With the addition of modified nano-aramid fiber, the tensile strength of the composite material of the photosensitive resin gradually increases. When the addition amount of modified nano-aramid fiber reaches 1%, the mechanical properties of the composite material of the photosensitive resin reach the maximum. When the addition amount of modified nano-aramid fiber exceeds this optimal mass ratio, the tensile strength of the composite material of the photosensitive resin decreases but is still higher than that of pure photosensitive resin. With the addition of modified nano-Al2O3, the tensile strength of the photosensitive resin composite material gradually increases. When the addition amount of modified nano-Al2O3 reaches 3%, the mechanical properties of the photosensitive resin composite material reach the maximum. When the addition amount of modified nano-Al2O3 exceeds this optimal mass ratio, the tensile strength of the photosensitive resin composite material decreases but is still higher than that of pure photosensitive resin. In summary, with the addition of silica filler, the tensile strength of the photosensitive resin composite material shows a trend of first increasing and then decreasing. When the addition amount of silica is 6%, the addition amount of modified nano-aramid fiber is 1%, and the addition amount of modified nano-Al2O3 is 3%, the tensile strength reaches the maximum value.

[0055] According to the mechanical simulation calculation of the composite material of photosensitive resin, the parts of the tensile parts that are prone to damage and failure are obtained (see Figure 5 ); Use SEM electron microscope to observe the tensile cross-section of photosensitive resin and its composite material to observe its failure state.

[0056] By monitoring the photosensitive resin and its composite materials with an electrochemical workstation, the curves of pure photosensitive resin and its composite materials under acidic conditions were obtained (see Table 1), and the following conclusions can be drawn: The photosensitive resin composite material is more acid-resistant than pure photosensitive resin. Under the same acidic environment, the photosensitive resin composite material corrodes more slowly.

[0057] By monitoring the photosensitive resin and its composite materials with an electrochemical workstation, the curves of pure photosensitive resin and its composite materials in an alkaline environment were obtained (see Table 1), and the following conclusions can be drawn: The alkali resistance of the photosensitive resin composite material is stronger than that of the pure photosensitive resin. Under the same alkaline environment, the corrosion rate of the photosensitive resin composite material is slower.

[0058] By monitoring the photosensitive resin and its composite materials with an electrochemical workstation, the curves of pure photosensitive resin and its composite materials in a saline environment were obtained (see Table 1), and the following conclusions can be drawn: The salt resistance of the photosensitive resin composite material is stronger than that of the pure photosensitive resin. Under the same salinity environment, the corrosion rate of the photosensitive resin composite material is slower.

[0059] Table 1 Corrosion potential and corrosion current density of photosensitive resins and their composite materials used in photocuring DLP technology under acidic, alkaline and saline conditions The corrosion resistance of photosensitive resin composite materials is higher than that of pure photosensitive resin. Under the same environment, the corrosion rate of photosensitive resin composite materials is lower than that of pure photosensitive resin.

Claims

1. A photosensitive resin for photocuring DLP technology, characterized in that: The raw materials of the photosensitive resin used for the photocurable DLP technology include epoxy resin matrix, acrylic acid substance, catalyst, inhibitor, photoinitiator and diluent; The epoxy resin matrix is ​​selected from one or more of E51 epoxy resin, E44 epoxy resin, F-51 epoxy resin or F-41 epoxy resin; and / or the acrylic substance is acrylic acid and / or acrylic acid; and / or the catalyst is selected from one or more of tetraethylammonium bromide, triphenyl antimony, and triethylamine; and / or the inhibitor is selected from one or more of p-hydroxyanisole, hydroquinone, and p-methoxyphenol; and / or the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and / or 1-hydroxy-cyclohexyl benzophenone; and / or the diluent is tripropylene glycol diacrylate and / or 1,6-hexanediol diacrylate.

2. The photosensitive resin for photocuring DLP technology according to claim 1, characterized in that: By mass ratio, photosensitive resin used in photocuring DLP technology: catalyst: inhibitor: photoinitiator: diluent = 100: (0.1~1): (0.01~1): (2~5): (15~25); by mass ratio, epoxy resin matrix: acrylic substance = (5~9): (1~5).

3. The method for preparing a photosensitive resin for photocurable DLP technology according to claim 1 or 2, characterized in that: The following steps are involved: S1: heating the epoxy resin matrix, adding acrylic substances, catalysts, and polymerization inhibitors, performing a gradient temperature increase reaction, and then cooling the temperature to obtain epoxy acrylate; S2: Epoxy acrylate, photoinitiator and diluent are mixed, ultrasonically dispersed, vacuumed and air bubbles removed to obtain a photosensitive resin for photocuring DLP technology.

4. The method for preparing a photosensitive resin for photocurable DLP technology according to claim 3, characterized in that: In the S1, the heating temperature is 80-90°C; the reaction temperature of the gradient temperature increase reaction is 90-100°C and kept warm for 1-3h, then the temperature is increased by 10°C and kept warm for 0.5-2h, and then cooled to 60-70°C; and / or, in the S2, the mixing and stirring is performed for more than 5min, and the ultrasonic dispersion is performed for more than 30min.

5. A composite material of photosensitive resin for photocuring DLP technology, characterized in that: The raw materials include the photosensitive resin for photocurable DLP technology as described in claim 1 or 2 and modified nanofillers, wherein the modified nanofillers are selected from one or more of modified nano-silicon dioxide, modified nano-aramid fiber and modified nano-Al2O3; according to the selection of modified nanofillers, the composite material of the photosensitive resin for photocurable DLP technology is one of photosensitive resin / silicon dioxide composite material, photosensitive resin / aramid fiber composite material and photosensitive resin / Al2O3 composite material.

6. The composite material of photosensitive resin for photocuring DLP technology according to claim 5, characterized in that: The composite material of photosensitive resin used in light-curing DLP technology has a tensile strength of 36.89~46.91MPa and an elongation at break of 22.7%~30.2%.

7. The method for preparing a composite material of a photosensitive resin for photocurable DLP technology according to claim 5 or 6, characterized in that: Use one of the following preparation methods: (1) When the composite material of the photosensitive resin used for the photocurable DLP technology is a photosensitive resin / silicon dioxide composite material, the preparation method adopted is: The epoxy resin matrix and the silica / epoxy resin mixed sol are mixed according to a ratio to obtain a diluted silica / epoxy resin mixed sol, and the diluted silica / epoxy resin mixed sol is replaced with the epoxy resin matrix to obtain a photosensitive resin / silicon dioxide composite material according to a preparation method of a photosensitive resin for a light-cured DLP technology; wherein the mass percentage of silica in the photosensitive resin / silicon dioxide nanocomposite material is 1% to 10%; (2) When the composite material of the photosensitive resin used for the light-curing DLP technology is a photosensitive resin / aramid fiber composite material, the preparation method adopted is: The modified nano-aramid fiber suspension is repeatedly washed with deionized water and a solvent, the collected modified nano-aramid fibers are added to a diluent solution, and the obtained mixture is dispersed using an ultrasonic cell disruptor to obtain uniformly dispersed modified nano-aramid fibers; The modified nano-aramid fiber and the photosensitive resin used for the light-curing DLP technology are mixed evenly, and then heated and vacuum degassed to remove the solvent to obtain a photosensitive resin / aramid fiber composite material; wherein the mass percentage of the aramid fiber in the photosensitive resin / aramid fiber composite material is less than or equal to 2%; (3) When the composite material of the photosensitive resin used for the light-curing DLP technology is a photosensitive resin / Al2O3 composite material, the preparation method adopted is: The modified nano-Al2O3 and the photosensitive resin used for the light-curing DLP technology are mixed and ultrasonically dispersed to obtain a photosensitive resin / Al2O3 composite material; wherein the mass percentage of Al2O3 in the photosensitive resin / Al2O3 composite material is 1% to 5%.

8. The method for preparing a composite material of a photosensitive resin for photocuring DLP technology according to claim 7, characterized in that: In preparation method (2), the modified nano-aramid fiber suspension is prepared by a top-down method; the solvent is ethanol and / or acetone; the ultrasonic cell disruptor dispersion time is 30-60 minutes; the mixing is performed by magnetic stirring for 30-60 minutes; the heating vacuum degassing is performed by vacuum degassing at 50-70°C for more than 24 hours; in preparation method (3), the modified nano-Al2O3 is prepared by a mechanochemical method; the ultrasonic dispersion has an ultrasonic power of 50-60W, an ultrasonic dispersion time of more than 24 hours, and an ultrasonic temperature of less than 40°C.

9. The use of the composite material of photosensitive resin for photocuring DLP technology according to claim 5 or 6, characterized in that: Used as raw material for photocuring DLP technology, and photocuring DLP technology is used to print application structural parts or test structural parts.

Citation Information

Patent Citations

  • Photosensitive resin compound material for ultralow-temperature resistant 3D printing and preparation thereof

    CN108546393A

  • Nanocomposite photosensitive resin for 3D printing and preparation method thereof

    CN108727786A

  • Chopped fiber reinforced photosensitive resin for 3D printing and preparation method thereof

    CN114045020A

  • Nano fibril cellulose reinforced photocuring 3D printing composite material and preparation method thereof

    CN114350117A